Feminist Research in Crimino-Legal Studies: Reflections on 'Absolute Rubbish' - K. Carrington (Law Text Culture, 2002)
This paper was initially written for an oral presentation at a seminar organised by the Legal Intersections Research Centre at the University of Wollongong. Translating it into a text form for a wider readership has not proved easy, given the lively, loud and gendered court-room dialogue upon which it draws is unable to be reproduced. The article commences with a brief sketch of some of the defining characteristics of research in feminist crimino-legal studies. This part of the paper assumes some familiarity with the epistemological debates that have hovered over social science research since the challenges of post-enlightenment philosophies to modernist knowledge claims. Then, reflecting on my own experiences as a witness subpoenaed before the Police Integrity Commission (PIC), the paper illustrates how the alignment between legal method with scientific positivism discredits feminist research in crimino-legal studies in much the same way as the legal process systematically disqualifies rape victims. I aim to demonstrate how this process of disqualification entails the asymmetrical arrangement of gendered bodies and spatiality in the hearing room, as well as the coercive exercise of a masculinist invalidation which operates through a micro-physics of power incompatible with the espoused judicial rhetoric of 'objectivity and neutrality'. The paper concludes with a salutary note about the future of feminist research in crimino-legal studies.